2018
DOI: 10.1093/nar/gky526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of histone H2B ubiquitylation on the nucleosome structure and dynamics

Abstract: DNA in nucleosomes has restricted nucleosome dynamics and is refractory to DNA-templated processes. Histone post-translational modifications play important roles in regulating DNA accessibility in nucleosomes. Whereas most histone modifications function either by mitigating the electrostatic shielding of histone tails or by recruiting ‘reader’ proteins, we show that ubiquitylation of H2B K34, which is located in a tight space protected by two coils of DNA superhelix, is able to directly influence the canonical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 96 publications
5
38
0
Order By: Relevance
“…In this study, we performed in vitro assays with the nucleosomes without histone modifications. Some histone modifications reportedly affect the nucleosome stability 58,59 . It is intriguing to study the relationship between histone modifications and RNA-mediated nucleosome destabilization.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we performed in vitro assays with the nucleosomes without histone modifications. Some histone modifications reportedly affect the nucleosome stability 58,59 . It is intriguing to study the relationship between histone modifications and RNA-mediated nucleosome destabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these results add another layer of complexity to the cross-talk, where H2B ubiquitination regulates the DOT1L-mediated nucleosome destabilization in addition to histone H3 Lys79 methylation. As previous works showed that H2B ubiquitination plays important roles in transcription elongation and nucleosome dynamics, DOT1L-mediated DNA unwrapping might facilitate this process (Wu et al 2014;Krajewski et al 2018;Lee et al 2018). At this moment, it is not clear how DOT1L binding induces the detachment of DNA with the concomitant disorder of the parts of histones.…”
Section: Dot1l Binding Destabilizes the Nucleosome Structurementioning
confidence: 93%
“…H2B ubiquitylation may also directly regulate transcription elongation by changing the chromatin structure. Although the role of H2B ubiquitylation in nucleosome stabilization seems to suggest the opposite effect 97 , 98 , several biochemical studies have shown that H2B ubiquitylation disrupts chromatin compaction and promotes an open chromatin structure 99 101 . H2B deubiquitylation has also been shown to have a profound effect on subsequent H3 methylation and productive transcription 14 , 15 , 88 , 89 , 102 , 103 .…”
Section: Functional Modules Of Sagamentioning
confidence: 99%